The banding in serpentinites and its influence on character of talc-magnesite and magnesite mineralization (natural and experimental data) - NASEDKIN, V. V.; MARKOV, V. K.; BOEVA, N. M.; KRUPENIN, V.K. (Boletim Paranaense de Geociências, 2002)
The geological setting of some banded talc-magnesite ores and magnesites was studied in the field (Urals, Russia; Finland, East Iran). Talc-magnesite and magnesite ores occur in ultramafic rocks. Experimental methods were used in order to determine the influence of physico-mechanical parameters on the formation of banded structures in talc-magnesite rocks and magnesites. Experiments were carried out with axial compression up to 10 kbar and confining pressure 2, 4, 6 and 8 kbars at room temperature. The samples were chemically analyzed using a Philips Analytical PW 2400 authomatic XRF Spectrometer and a scanning electron microscope (SEM). Some analyses were made with a "Camebax SX-50" electron microprobe, using an accelerating voltage of 20 kilovolts for all elements with a sample current of 20 nanoamps. X-ray method for phase identification was used. Structure peculiarities of rocks prior to the experiment and after were studied by optical methods in polished sections and thin sections. It was shown, that banding in talc-magnesite stone and magnesites are inherited from banded serpentinites and can affect on distribution and composition rock-forming minerals.